Asymmetric total synthesis of (−)-(3R)-inthomycin C - Balcells, S; Haughey, M; Walker, J; Josa-Cullere, L; Towers, C; Donohoe, T (American Chemical Society, 2018)
A short (10 step) and efficient (15% overall yield) synthesis of the natural product (−)-(3R)-inthomycin C is reported. The key steps comprise three C–C bond-forming reactions: (i) a vinylogous Mukaiyama aldol, (ii) an olefin cross-metathesis reaction, and (iii) an asymmetric Mukaiyama–Kiyooka aldol. This route is notable for its brevity and has the advantage of lacking stoichiometric tin-promoted cross-coupling reactions present in previous approaches. Initial investigations on the biological activity of (−)-(3R)-inthomycin C and structural analogues on human cancer cell lines are also described for the first time.